PENGARUH PELATIHAN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN DI KANTOR KELAUTAN DAN PERIKANAN KABUPATEN BOALEMO - Nur Rahmi Nur Rahmi; Agus Susanto Naue (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to determined how much influence Training (X1) and Job Placement (X2) both simultaneously and partially on Employee Performance (Y) at the Office of the Marine and Fisheries Office of Boalemo Regency. Using survey methods, data collection methods using questionnaires to respondents. Analysis using Path Analysis. The results shown that training (X1) and Job Placement (X2) simultaneously had a significant effect on employee performance (Y) at the Office of Marine Affairs and Fisheries in Boalemo Regency of 0.390 (39%). Meanwhile, 0.610 (61%) is influenced by outside variables that are not studied. Training (X1) partially has a significant effect on Employee Performance (Y) of 0.000. Job Placement (X2) partially does not have a significant effect on Employee Performance (Y) of 0.726.Keywords: Training ; Job Placement; Employee Performance